Italy : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper for Italy presents updated estimates of potential growth for Italy, using new techniques that draw on co-movements of output, employment, and inflation over the business cycle to distinguish trends from cycles. The paper provides an assessment of an area-corporate governance-that has important implications not only for trend growth but also for macrofinancial developments. The paper reviews developments in fiscal federalism in Italy and draws on cross-country experience to offer suggestions on how the decentralization process now under way can be most effectively managed.